RESEARCH OF LUBRICATING ABILITY OF THE MATERIALS USED AT THE DEVELOPMENT OF LUBRICANTS STRUCTURES FOR CASTING OF ALUMINUM ALLOYS UNDER PRESSURE - A. A. Pivovarchik; A. M. Mihaltsov (Литьë и металлургия, 2012)
The research of lubricating ability of new “alternative” materials used in composition of separating coverings at molding of aluminum alloys under high pressure is carried out in the present work.